Types of Unmanned Aerial Vehicles (UAVs), Sensing Technologies, and Software for Agricultural Applications - Sri Charan Kakarla; Yiannis Ampatzidis (EDIS)
This publication provides detailed information about the most used UAVs, sensing technologies, and software for agricultural applications. Written by Sri Charan Kakarla and Yiannis Ampatzidis, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2021.